Effect of temperature on sporulation and spore development of giant kelp (Macrocystis pyrifera) - Duong M. Le; Mathew J. Desmond; Daniel W. Pritchard; Christopher D. Hepburn (PLoS ONE, 2022)
Rising ocean temperature is a major driver of kelp forest decline worldwide and one that threatens to intensify over the coming decades. What is not particularly well understood are the mechanisms that drive loss and how they operate at differing life stages. This study aimed to establish an understanding of the effects of increasing temperature on the early developmental stages of the giant kelp, Macrocystis pyrifera. Sporulation was carried out across 10 temperature treatments from 9.5 to 26.2°C ± 0.2°C at approximately 2°C intervals. Spores were then incubated at these temperatures under a 20.3±1.7 μmol photons m-2 s-1, 16L:8D photoperiod for 5 days. Results indicate that spore release was positively correlated with increasing temperature, whereas an inverse trend was observed between temperature and the growth of germ-tube. The thermal threshold for spore and germling development was determined to be between 21.7°C and 23.8°C. Spore settlement was the most drastically effected developmental phase by increasing temperature. This study highlights the vulnerability of early life stages of M. pyrifera development to rising ocean temperature and has implications for modelling future distribution of this valuable ecosystem engineer in a changing ocean.